Key buildings from prehistory to the present : plans, sections and elevations - Ballantyne, Andrew (London : Laurence King Pub., 2012)
Features around 150 of the most significant buildings in the history of world architecture, from the pyramids and the Parthenon to some of the most important works by recent architects.
Includes bibliographical references and index
Keywords: Architectural design; Architecture -- Designs and plans; Architecture -- History